THE POTENTIAL OF SITUATIONAL JUDGEMENT TEST AS AN INSTRUMENT OF ETHICAL COMPETENCE ASSESSMENT: A LITERATURE REVIEW - Hikmah Muktamiroh; Herqutanto Herqutanto; Diantha Soemantri; Agus Purwadianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Agreement on the importance of teaching and assessing ethical competence as part of professionalism in medical education continues to grow. The assessments of ethical competence at the “does” level in preclinical students or a large group of resident candidates are considered less efficient and expensive. It is necessary to find an alternative form of ethical competence assessment instrument as a complementary test at the level “knows how” before being tested at the level “does.” This research proposed investigating the Situational Judgement Test (SJT) potential and obtaining evidence of the SJT as an instrument of ethical competence assessment.Methods: This study was a literature review of 39 journal articles relating to SJT, obtained through PubMed data-based and google scholar search engine.Results: There was evidence of the use of SJT to assess ethical competence. Ethical competence can be evaluated by ethical decisions making ability. SJT containing procedural skills in ethical decisions making. SJT having good values as deliberation in ethical dilemmas and idealistic ethical ideology (conative test) also exists. These findings support the evidence of potential SJT to assess ethical competence.Conclusion: SJT can be used to assess ethical competence at the level “knows how” before being tested at the level “does” based on the following reasons: SJT can contain content questions that are conative, SJT can assess the ability of ethical decision making based on an assessment of procedural knowledge related to ethical deliberation of ethical decision making in ethical dilemmas.